Development of the COVID-19 Stigma Scale: Validity and Reliability Study - Bahadır Geniş; Mustafa Yıldız (Gazi Medical Journal)
Objective: Stigmatization leads to severe consequences both individually and socially. This situation can also occur in epidemics and complicate the treatment process. Therefore, the objective evaluation of stigma and the creation of an action plan on this issue are the most basic steps in the fight against the epidemic. This study aimed to develop and study the reliability and validity of a scale that evaluates stigma against individuals who experienced coronavirus disease-2019 (COVID-19). Methods: A 24-item draft scale was prepared by considering the stigma experienced by individuals who experienced COVID-19 both in their close relations and social environment. The study was conducted on the relatives of patients referred to Kocaeli University Faculty of Medicine Hospital’s different polyclinics. In addition to the developed COVID-19 Stigma Scale (CSS), the COVID-19 Information Questionnaire (CIQ) was used. Results: The sample of the study consisted of 323 healthy individuals who were 54.5% male, with a mean age of 39.0±13.7 years. In the factor analysis, which included 24 items, five items with a factor load below 0.40 were eliminated. The final version of the scale consisted of three factors, and these factors (rejection, discrimination, and emotional reactions) explained 61% of the total variance. Cronbach’s alpha coefficient for the total CSS was calculated as 0.91. A significant negative correlation was found between the CSS total and CIQ total scores (r=-0.301, p<0.001). Conclusion: The CSS is valid and reliable in assessing the stigmatization of individuals in the healthy population toward COVID-19 patients.